Motor intervention and assessment instruments in Autism Spectrum Disorders - Lourenço, Carla (2020)
Abstract The practice of physical activity in people with disabilities provides important health benefits (Wind, Schwend, & Larson, 2004; Chanias, Reid, & Hoover, 1998), particularly in individuals with autism spectrum disorder (ASD). Several motor interventions have been suggested as beneficial for this population. Considering this variety, it is important to synthesize the different existing programs, the population in which they are applied. This research aims to review the motor interventions used in children with ASD, as well as the evaluation methods used, so that it becomes clear what the options are for motor work with this population. All the studies presented showed improvements in participants. A literature search was conducted in Web of Science, SCOPUS and Google Scholar 2013, to include research studies that evaluate motor intervention in children with ASD. Fifteen studies meet inclusion criteria. Results show that motor intervention programs that have been carried out are quite diverse, from dance, trampoline training, balance training or fundamental motor skills, for example, to evaluate motor skills which used different test batteries, one of the most common is the motor proficiency test of Bruininks-Oseretsky. On the other hand, other methods were used to evaluate the social interaction like Gilliam Autism Rating Scale or Autism Rating Scale. We conclude that to improve the motor fitness of children with ASD different strategies can be followed. As the revised programs use different evaluation tools, it is difficult to compare the results obtained with each other. A motor intervention that comprises different types of exercises and materials, using ludic exercises may be a potentially more effective strategy.